2018
DOI: 10.1016/j.cllc.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes in OAK: A Phase III Study of Atezolizumab Versus Docetaxel in Advanced Non–Small-cell Lung Cancer

Abstract: These PRO data support the clinical benefit of atezolizumab in patients with previously treated advanced or metastatic NSCLC. Atezolizumab prolonged the TTD of patients' limitations in role and physical functions compared with docetaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 25 publications
7
60
1
2
Order By: Relevance
“…All trials had overall survival or progression-free survival as the primary endpoint; all reported significant differences in one of these endpoints between treatment arms. HRQOL was a secondary endpoint in nine trials [49,50,51,52,53,54,55,56,57], an exploratory endpoint in five RCTs [58,59,60,61,62] and for one trial it was unclear if the HRQOL endpoints were secondary or exploratory [63]. Seven trials discussed HRQOL in their main publication [50,59,60,52,61,56,57].…”
Section: Key Characteristics Of Identified Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…All trials had overall survival or progression-free survival as the primary endpoint; all reported significant differences in one of these endpoints between treatment arms. HRQOL was a secondary endpoint in nine trials [49,50,51,52,53,54,55,56,57], an exploratory endpoint in five RCTs [58,59,60,61,62] and for one trial it was unclear if the HRQOL endpoints were secondary or exploratory [63]. Seven trials discussed HRQOL in their main publication [50,59,60,52,61,56,57].…”
Section: Key Characteristics Of Identified Trialsmentioning
confidence: 99%
“…The conceptual measurement and methodology for evaluating HRQOL outcomes from the 15 RCTs included in this systematic review are summarised in Table 2 and S2 Table. HRQOL was Health-related quality of life assessment, cancer and immune checkpoint inhibitors: A systematic review , to satisfy the "a priori hypothesis stated" criterion, the study needed to predefine HRQOL end point and/or state expected changes because of the specific treatment. Only five trials of the 15 RCTs satisfied this criterion but none of them included an a priori hypothesis for the expected HRQOL outcomes [49,50,51,54,55].…”
Section: Quality Of Hrqol Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OAK trial also demonstrated that patients who received atezolizumab reported a higher health-related quality of life at baseline compared with the patients who received docetaxel. 32 This was the first study that indicated improved survival benefits with atezolizumab in NSCLC.…”
Section: Second-line Immune Checkpoint Inhibitionmentioning
confidence: 99%
“…Nos casos em que a expressão de PD-L1 é superior a 50%, o pembrolizumab tornou-se mesmo o fármaco de primeira linha, após aprovação do estudo Keynote 024, 4 com um perfil de toxicidade muito inferior aos dos esquemas de quimioterapia (QT), à base de platino, utilizados. Em segunda linha, três fármacos de imunoterapia estão aprovados (pembrolizumab, 5 nivolumab 6 e atezolizumab 7 ).…”
Section: Introductionunclassified